2017
DOI: 10.1371/journal.pone.0183615
|View full text |Cite
|
Sign up to set email alerts
|

Proteome dynamics and physiological responses to short-term salt stress in Leymus chinensis leaves

Abstract: Salt stress is becoming an increasing threat to global agriculture. In this study, physiological and proteomics analysis were performed using a salt-tolerant grass species, Leymus chinensis (L. chinensis). The aim of this study is to understand the potential mechanism of salt tolerance in L. chinensis that used for crop molecular breeding. A series of short-term (<48 h) NaCl treatments (0 ~ 700 mM) were conducted. Physiological data indicated that the root and leaves growth were inhibited, chlorophyll contents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
3
20
1
Order By: Relevance
“…This indicated that AMF inoculation increased the chlorophyll contents, which was consistent with our proteomics results. Similar results were also found in L. chinensis by Li et al (). On the basis of the proteomic analysis, we found that several proteins involved in chlorophyll synthesis were up‐regulated after AMF inoculation under AS (AS‐AM vs. AS analysis).…”
Section: Discussionsupporting
confidence: 90%
“…This indicated that AMF inoculation increased the chlorophyll contents, which was consistent with our proteomics results. Similar results were also found in L. chinensis by Li et al (). On the basis of the proteomic analysis, we found that several proteins involved in chlorophyll synthesis were up‐regulated after AMF inoculation under AS (AS‐AM vs. AS analysis).…”
Section: Discussionsupporting
confidence: 90%
“…Under saline conditions, plants adapt themselves by osmotic adjustment, accumulation of osmoprotectants, modifications in ion transport to avoid ion toxicities, and activation of enzymes by changing gene expression (Akram et al, 2006;Athar et al, 2015). Various genes or proteins form a regulatory network to modulate such physiological or biochemical processes under abiotic stress conditions (Ibrahim et al, 2016;Li et al, 2017;Farooq et al, 2018). Under saline conditions, plants may synthesize and accumulate certain stress specific proteins which directly reveal alteration or switching on/off the possible number of salt stress related genes (Zhang et al, 2012;Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Various genes or proteins form a regulatory network to modulate such physiological or biochemical processes under abiotic stress conditions (Ibrahim et al, 2016;Li et al, 2017;Farooq et al, 2018). Under saline conditions, plants may synthesize and accumulate certain stress specific proteins which directly reveal alteration or switching on/off the possible number of salt stress related genes (Zhang et al, 2012;Li et al, 2017). Identification of new proteins responsible for salinity stress tolerance may help in understanding detailed mechanism of salt tolerance in plants (Li et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations